REPREZENTACJE SPOŁECZNE WIELOJĘZYCZNOŚCI STUDENTÓW FILOLOGII ROMAŃSKIEJ - Kucharczyk, Radosław (Neofilolog, 2019)
The aim of this paper is to show the social representation of plurilingualism among students of French. The theoretical part of the paper presents definitions of plurilingualism used in sociolinguistics and foreign language didactics. The experimental part presents a survey conducted among the students, as well as a comparison of the results with the outcomes of a similar survey conducted in 2003, in order to indicate possible differences or changes in the didactic paradigm. The purpose of the study was to analyse the concept of plurilingualism, and to find to what extent students regard themselves as plurilingual.